2008
DOI: 10.1063/1.2898523
|View full text |Cite
|
Sign up to set email alerts
|

Transport of O+ through argon gas

Abstract: New experimental and theoretical results are presented that address the movement of O+ ions through argon gas. On the experimental front, improved ion mobility results are presented. These results confirm the presence of the oft-cited mobility minimum as a function of electrostatic field strength at room temperature. On the theoretical side, high-level ab initio potential energy curves are calculated for the Ar-O+ system and, from these, transport properties are calculated and compared to experiment. A crossin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…In previous work [9,45,46] we have concluded that the experiment conditions can affect the mix of spin-orbit states owing to incomplete thermalization; in such cases the ions were generally produced in a very energetic source, such as electron bombardment. In the present case the results in Figure 5 are fairly conclusive that only the 2 P1/2 state is populated to any great extent in the experiment.…”
Section: (F) Transport Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work [9,45,46] we have concluded that the experiment conditions can affect the mix of spin-orbit states owing to incomplete thermalization; in such cases the ions were generally produced in a very energetic source, such as electron bombardment. In the present case the results in Figure 5 are fairly conclusive that only the 2 P1/2 state is populated to any great extent in the experiment.…”
Section: (F) Transport Coefficientsmentioning
confidence: 99%
“…The cross sections as a function of collision energy were used in the program GC [31,33,34] to determine the reduced mobility, K0, and the other gaseous ion transport coefficients as functions of E/n0…”
Section: (B) Transport Coefficientsmentioning
confidence: 99%
“…Two different sets of data were taken. The first used the same configuration of the apparatus that was used in earlier measurements 87 of the mobility of O + in He. Here, ions generated by a pulsed electron impact ion source are passed through an "injection mass filter" (in actuality, a radio-frequency quadrupole mass filter) before being injected into the drift region through a small orifice.…”
Section: Experimental Mobilitiesmentioning
confidence: 99%
“…These calculations are based on the GramCharlier method [122,123] for solving the Boltzmann equation…”
Section: Viehland Databasementioning
confidence: 99%